Investigating potential mining induced water stress in Ghana's north-west gold province - Moomen, Abdul-Wadood; Dewan, Ashraf (2016)
This study investigates the potential interactions of mining industry activities with water sources. The investigation identifies the socioeconomic impacts, as demands for water for domestic and industrial purposes are expected to increase. A case study was conducted in Ghana's North-West, one of the country's emerging gold provinces. Data were obtained from both primary and secondary sources. Socioeconomic and mean monthly rainfall data were integrated with data on 124 boreholes, and locations of 45 dams and ponds. The criticality ratio was modified and used to estimate groundwater stress indices (GWSI) for the region. A minimum of 0.008 and a maximum of 0.016 groundwater stress indices were obtained. Aridity indices were also estimated and used to develop an iso-aridity map for the area. It was found that a maximum of 229 and a minimum of eight rural households would potentially be affected due to growing water stress. With the emergent use of water in mine operations, conflicts may arise between local communities and companies, and between neighbouring states. The results of this study provide baseline information that could be useful to stakeholders for informed decision-making and the management of mining-related water use conflicts in developing countries.